Avoidance‐based human Pavlovian‐to‐instrumental transfer. Issue 12 (10th October 2013) - Lewis, Andrea H.; Niznikiewicz, Michael A.; Delamater, Andrew R.; Delgado, Mauricio R.
Abstract The Pavlovian‐to‐instrumental transfer (PIT) paradigm probes the influence of Pavlovian cues over instrumentally learned behavior. The paradigm has been used extensively to probe basic cognitive and motivational processes in studies of animal learning. More recently, PIT and its underlying neural basis have been extended to investigations in humans. These initial neuroimaging studies of PIT have focused on the influence of appetitively conditioned stimuli on instrumental responses maintained by positive reinforcement, and highlight the involvement of the striatum. In the current study, we sought to understand the neural correlates of PIT in an aversive Pavlovian learning situation when instrumental responding was maintained through negative reinforcement. Participants exhibited specific PIT, wherein selective increases in instrumental responding to conditioned stimuli occurred when the stimulus signaled a specific aversive outcome whose omission negatively reinforced the instrumental response. Additionally, a general PIT effect was observed such that when a stimulus was associated with a different aversive outcome than was used to negatively reinforce instrumental behavior, the presence of that stimulus caused a non‐selective increase in overall instrumental responding. Both specific and general PIT behavioral effects correlated with increased activation in corticostriatal circuitry, particularly in the striatum, a region involved in cognitive and motivational processes. These results suggest that avoidance‐based PIT utilizes a similar neural mechanism to that seen with PIT in an appetitive context, which has implications for understanding mechanisms of drug‐seeking behavior during addiction and relapse.